2022
DOI: 10.1097/qad.0000000000003227
|View full text |Cite
|
Sign up to set email alerts
|

How informal healthcare providers improve uptake of HIV testing: qualitative results from a randomized controlled trial

Abstract: Objective: Uganda is HIV-endemic with a prevalence of 5.7%. Lack of epidemic control has been attributed to low engagement with HIV testing. Collaborating with informal healthcare providers, such as traditional healers, has been proposed as a strategy to increase testing uptake. We explored acceptability and implementation of an HIV testing program where traditional healers delivered point-of-care testing and counseling to adults of unknown serostatus (clinicaltrials.gov NCT#03718871).Methods: This study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…While there is observational evidence suggesting that TH can be leveraged as lay providers to improve engagement in HIV care, there is a dearth of systematic trials addressing this subject [ 34 , 39 , 74 76 ]. This clinical trial is essential for definitively evaluating the impact of TH-supported care on HIV suppression in rural communities and optimizing the allocation of programmatic resources to low-income contexts.…”
Section: Discussionmentioning
confidence: 99%
“…While there is observational evidence suggesting that TH can be leveraged as lay providers to improve engagement in HIV care, there is a dearth of systematic trials addressing this subject [ 34 , 39 , 74 76 ]. This clinical trial is essential for definitively evaluating the impact of TH-supported care on HIV suppression in rural communities and optimizing the allocation of programmatic resources to low-income contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, traditional healers may be preferred as they are more accessible in communities compared with biomedical healthcare facilities, where HIV clinical treatment facilities carry stigma [50]. We and others have also shown that patients choose to receive care from traditional healers instead of medical clinics due to trusting relationships with healers and the perception that healers provide more psychosocial support [34,36,[52][53][54]. Modern medicine has also been criticized for failing to resolve all health problems, and thus, traditional medicine promises to fill the void in the biomedicine health care system [51].…”
Section: Discussionmentioning
confidence: 99%
“…TH are informal healthcare providers and trusted community members who may be uniquely positioned to bridge the rural HIV treatment gap. Qualitative data from multiple countries suggest that TH are among the most accessible and trusted providers in rural communities, where the majority of Africans reside [ 7 12 ]. TH often serve as the first line of healthcare for rural PLWH, some of whom prefer healers’ care alone, and some of whom utilize both TH and clinic-based care [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%